MONITORING THE ABUNDANCE OF Vibrio sp. BACTERIA IN THE WATER OF VANAME SHRIMP (Littopanaeus vannamei) BREEDING POND AT JEPARA BRACKISH WATER AQUACULTURE CENTER - Trianingtyas, Laela; Ufianah, Ufianah; Ratnaningsih, Navita Desy; Kasprijo, Kasprijo; Riady, Reza Muhammad; Rizkiyanti, Ita; Zainuddin, Muhammad (PT. Artha GenetikaLab Indonesia, 2024)
The presence of vibrio bacteria in the breeding pond is one of the important factors that affect the activities of vaname shrimp breeding. Vibrio sp. bacteria in waters can cause losses if the number is above the threshold that should be. The high abundance of Vibrio sp. bacteria in the cultivation environment is an indicator that shows the potential for disease that can reduce the growth rate and survival of shrimp. The purpose of the study was to determine the abundance and dominance of vibrio bacteria in vaname shrimp breeding ponds using the TPC (Total Plate Count) calculation technique. The methods used include bacterial sampling, preparation of tools and materials, making bacterial culture media (NA and TCBS), dilution, bacterial inoculation, and calculating the number of bacterial colonies. The results of the calculation of bacterial abundance showed that there were 9 breeding ponds with different abundances. The highest abundance was found in pond BV1 with a total bacterial value of 9.6 x 105 CFU/ml. Meanwhile, the highest vibrio dominance was found in pond BV4 with a percentage of 43.69%.